The Influence of Digital Competencies, Learning Communities, And Supervision on Teacher Performance That Impact Work Achievement in Pangkalpinang City Primary Schools - Silvia Dwi; Juhari; Mohamad Makrus; Efendi Sugianto (Edusight International Journal of Multidisciplinary Studies, 2025)
This research aims to analyze the influence of digital competence, learning communities, and supervision on teacher performance which impacts work performance in elementary schools (SD) in Pangkalpinang City. The research uses an explanatory approach to explain causal relationships between variables. The model applied is hypothesis testing based on theories developed by the researcher. Primary data was collected through questionnaires distributed to elementary school teachers in SD Negeri 3, 6, 10, and 28 Pangkalpinang. The data were analyzed using Structural Equation Modelling (SEM) with the SmartPLS 4 software. The research findings indicate that digital competence, learning communities, and supervision significantly influence teacher performance. Furthermore, these three variables also have a positive and significant impact on work performance. The study also reveals that digital competence, learning communities, and supervision not only directly affect work performance but also indirectly through improvements in teacher performance. Therefore, enhancing digital competence, strengthening learning communities, and implementing effective supervision can significantly improve teacher performance, ultimately leading to better overall work performance in elementary schools